A Development and Implementation of Integrated STEM-Based Science Textbooks and Local Potential of Coffee Agroecosystems to Improve Science Literacy for Junior High School Students - Mohammad Abdul Azis; Sudarti Sudarti; Bevo Wahono; I Ketut Mahardika; Slamet Hariyadi (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
The purpose of this research is to describe the characteristics of STEM-based teaching materials and to find out the increase in scientific literacy skills of junior high school students. The method used in this research is research and development. The design of this study uses the ADDIE model, with the stages of analysis, design, development, implementation, and evaluation. The trial design used the One Group Pretest-Posttest Design. The test subjects were class VII SMP Walisongo Mayang. The characteristics of this integrated STEM-based textbook and local potential contain material on temperature and heat, complemented by student environmental events as well as practicum procedures and project creation related to STEM aspects for students. The results of the validity of the textbooks developed by the validator show very valid criteria, with the results of the feasibility test using a student response questionnaire showing textbooks included in the practical category and good for students. As well as the results of the effectiveness of textbooks show that they can improve students' scientific literacy skills which are marked by an increase in pretest to posttest scores (t-test value 25,668 and n-gain 0.77). Developing textbooks for students makes it possible to develop them more broadly with STEM development as well as the problems and challenges faced by students in the surrounding environment.